Credit bubbles and land bubbles - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2010)
In modern macroeconomic models it is difficult to obtain explosive price bubbles on assets with positive net supply. This paper shows that it is possible to obtain explosive bubbles in certain situations when assets such as land are used as collateral and lenders are willing to lend freely against it. As land prices rise, collateral constraints become relaxed, and households wish to borrow more. If the financial sector or government is willing to accommodate this by issuing credit indefinitely, this can lead to self-fulfilling equilibria where land has a positive, purely speculative, value. Furthermore, such bubbles need not affect real allocations in the absence of other market imperfections, even when land is a factor in production.
Keywords: G12; E52; E62; 330; Immobilienpreis; Kreditsicherung; Bubbles; Kredit; Bodenspekulation; Budgetrestriktion; Theorie